Magnets ingestion as a rare cause of ileus in adults: A case report - Doklestić Krstina; Lončar Zlatibor; Jovanović Bojan; Veličković Jelena (Vojnosanitetski Pregled)
Introduction. Magnetic foreign bodies are harmless when ingested as a single object. However, if numerous of individual magnets are ingested at certain intervals, one after the other, they may attract each other through the bowel wall and cause severe bowel damage. Case report. We re-ported a case of a man, age 21, who swallowed 2 very small magnets, presented with clinical and radiographic signs of acute bowel obstruction and intestinal fistula. The cause of obstruction was detected during laparotomy. At laparotomy, one magnet was found in the proximal jejunum and the other in the distal ileum, strongly attracting each other followed by small bowel twisting around this point of rotation, causing a complete small bowel obstruction with strangulation and jejuno-ileal fistula. The intestinal segments were devolvulated and both intestine perforations were primarily sutured. The patient recovered successfully after the surgery and was discharged 5 days after the laparotomy. Conclusion. Patients who ingested magnetic objects must be seriously considered and emergency laparotomy should be performed to prevent serious gastrointestinal complications.